AN INVESTIGATION OF THE IMPACT OF COMPETITIVE STRATEGY ON EXPORT PERFORMANCE: A LITERATURE REVIEW IN THE PERIOD 1998 - 2018 - Njegić, Katarina (Radosavljević); Ravić, Nenad (International Journal of Economic Practice and Policy, 2020)
Competitive strategy is considered to be one of the most important determinants of export performance (EP). The last literature review on the link between competitive strategy and EP was provided by Zou and Stan (1998) based on empirical papers published from 1987 until 1997. The aim of this paper is to uncover scientific findings in this field in the period 1998-2008. In order to find empirical studies published in the observed period, a computer and manual bibliographic search was used. In total, 17 empirical studies on the observed topic were revealed. In order to systematize the results of the found studies, a vote-counting technique was used, supplemented with a narrative approach. Several gaps in the literature have been identified and based on them the recommendations for further research in this area are proposed.